2007
DOI: 10.1007/s00531-007-0211-1
|View full text |Cite
|
Sign up to set email alerts
|

Salinization of groundwater in the North German Basin: results from conjoint investigation of major, trace element and multi-isotope distribution

Abstract: Conjoint consideration of distribution of major, rare earth elements (REE) and Y (combined to REY) and of H, O, C, S, Sr isotopes reveals that four types of groundwater are distinguishable by their chemical composition presented by spider patterns. REY patterns indicate thermosaline deep water and two types of shallow saline groundwaters. Presence of connate waters is not detectable. Sr isotope ratios distinguish three sources of Sr: fast and slow weathering of biotite and K-feldspar in Pleistocene sediments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 47 publications
(56 reference statements)
5
35
0
Order By: Relevance
“…In particular, observed processes confirm hypothesizes suggested by previous hydrochemical studies [Tesmer et al, 2007;Möller et al, 2008]. The results corroborate major conclusions derived by previous two-dimensional numerical simulations , at the same time providing insights in novel aspects of the hydrodynamics of the system.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In particular, observed processes confirm hypothesizes suggested by previous hydrochemical studies [Tesmer et al, 2007;Möller et al, 2008]. The results corroborate major conclusions derived by previous two-dimensional numerical simulations , at the same time providing insights in novel aspects of the hydrodynamics of the system.…”
Section: Discussionsupporting
confidence: 89%
“…Following Möller et al [2008], an ascending flow component is the likely cause of the observed shallow salinization. This was not possible to be confirmed based on the results from previously published two-dimensional numerical investigations.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, due to lower diversity of fermentative bacteria compared with the SRB and low DOC content in fluids, hydrogen release from fermentation processes was probably not that relevant than chemical corrosion. Besides 16S rRNA gene sequences assigned to SRB, the isotopic signature of the residual sulfate (δ 34 S(SO 4 ) > 30 ‰, Möller et al 2008), a 10 % lower sulfate content in fluids produced from the cold well, and the detection of sulfide precipitates in topside facility filters (Fig. 4) clearly indicate metabolically active SRB.…”
Section: Discussionmentioning
confidence: 99%